Belling the cat: Eli F. Heckscher on the gold standard as a discipline device - Klas Fregert (Lund University, School of Economics and Management, Department of Economics, 2011)
Unlike Knut Wicksell, Eli Heckscher did not believe the time had arrived for "managed money" to replace the gold standard after World War I. The war had shown that only a gold standard could bind the central bank to a time-consistent policy with reasonable price stability. Heckscher likened the problem of reinstating the gold standard to "Belling the cat" in Aesop's fable. When the international gold standard crumbled in the Great Depression, he supported the Swedish price stabilization regime as a temporary system. Heckscher was an early discoverer of the time-consistency problem in monetary policy and hence stressed the importance of the institutional framework of monetary policy.
Keywords: B22; E31; E42; 330; Heckscher; time-consistent policy; devaluation; deflation; gold standard